Anti-inflammatory potential of mung bean seed coat water extract in lipopolysaccharide-induced 3T3-L1 adipocytes - Buathong, Norathee; Chandarajoti, Kasemsiri; Sae-tan, Sudathip (Agriculture and Natural Resources, 2021)
Excessive lipid accumulation in adipocytes results in low-grade inflammation, which is a major cause of many chronic diseases including metabolic syndromes, hypertension, diabetes and cardiovascular diseases. The prolonged lipid accumulation causes the production of inflammatory enzymes, pro-inflammatory cytokines and free radicals. Many plant extracts rich in polyphenols have reported anti-inflammatory activities. In this study, mung bean seed coat, a by-product from the mung bean industry, was extracted with boiling water to obtain mung bean seed coat water extract (MSWE). The MSWE contained high amounts of polyphenols (mean ± SD, 4.39 ± 0.01 mg gallic acid equivalents/g of dry weight extract). The anti-inflammatory activity of MSWE was investigated in lipopolysaccharide-stimulated 3T3-L1 adipocytes. MSWE had 2,2 diphenyl-1-picrylhydrazyl scavenging activity (half maximal inhibitory concentration value of 234 μg/mL). Low doses of MSWE (6.25 μg/mL or 12.5 μg/mL) reduced intracellular reactive oxygen species. In addition, MSWE decreased cyclooxygenase 2 and increased inducible nitric oxide synthase mRNA expressions. In addition, MSWE reduced the mRNA expression of pro-inflammatory cytokines (interleukin (IL)-1β, IL-6 and tumor necrosis factor, TNF-α). Low doses of MSWE (6.25 μg/mL or 12.5 μg/mL) increased the mRNA expression of IL-10. In conclusion, MSWE exerted anti-inflammatory potential via the modulation of inflammatory enzymes and inflammatory cytokines as well by free radical scavenging activity. The results suggested that MSWE was beneficial in alleviating inflammatory diseases and would be suitable as a functional food.